Pengembangan Aplikasi Berbasis Data untuk Optimalisasi Posyandu Pucuk Rebung Bersiku Keluang - Yolanda, Anne Mudya; Erda, Gustriza; T, Nurhannifah Rizky; Finda, Ingla; Tata, Tata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Integrated Service Posts (Posyandu) play an important role in improving community health, especially in rural and remote areas. Posyandu provides basic health services for mothers and children, including growth monitoring, pregnancy check-ups, immunizations, and counseling on nutrition and health. However, many Posyandu, including Posyandu Pucuk Rebung Bersiku Keluang in Sail Sub-district, Pekanbaru, still use a manual recording system in data management. This often results in inaccurate data and makes it difficult to make informed decisions, which in turn hinders effective health policy development. This service activity aims to design and implement an information system specifically for Posyandu, with a focus on data digitization to facilitate recording, management, and visualization of information. The system is expected to provide more accurate data and comprehensive information on maternal and child health conditions. With a user-friendly dashboard-based design, the system is expected to improve the efficiency of data management and support more informed decision-making at the local level. The program is also expected to have a positive impact on the quality of health services in Posyandu and provide recommendations for similar implementation in other Posyandu.